Pembentukan Kesadaran Gender pada Anak Usia Dini: Perspektif Teori Ekologi Bronfenbrenner - Nurmiati, Dwi Rahayu (Universitas Al Azhar Indonesia, 2025)
Early Childhood Education plays a crucial role in shaping gender awareness from an early age. This study aims to analyze how the social environment in PAUD contributes to children's understanding of gender based on Bronfenbrenner’s Ecological Systems Theory. A literature review method was used to examine relevant studies. The findings indicate that each ecological system microsystem, mesosystem, exosystem, macrosystem, and chronosystem contributes to shaping children’s gender perception. The microsystem, including family and school, directly influences how children understand gender roles, while the mesosystem, exosystem, and macrosystem establish norms and policies affecting gender education in PAUD. This study also identifies challenges in implementing gender-based education, such as bias in teaching materials, lack of teacher training, and cultural and social norms. Therefore, a comprehensive strategy is needed through gender integration in the curriculum, teacher capacity building, and active parental involvement in supporting inclusive gender education.Keywords - Bronfenbrenner’s Ecological Theory, Early Childhood Education, Gender Awareness, Inclusive Education.